Hypnerotomachia Poliphili: enigma o successo editoriale? .......... 253 - Pietrzak-Thébault, Joanna (Tra l’antica sapientia e l’imaginatio: Nuovi studi sul Polifilo, 2020)
The edition of the Hypnerotomachia Poliphili by the Venetian Publishing House of Aldus Manutius in 1499 raises many questions about the editorial collaborators of the House who are also the real co-authors of the masterpiece as well as theses about its place in the editorial and financial policy of the Torresani’s and Aldus’s House. This edition also focuses on some matters such as experiments with the new vernacular literary language in the period of intellectual and typographical crisis, the need of the new synthesis of knowledge and the search for relations between intellectuals and aristocracy that a printed book, as a new medium, could ensure. This publication seems to be just on the cross-roads of all these tendencies, however difficult to detect, as they are random revealed by documents or letters. The second edition, issued by the House in 1545, using a new font but almost every original woodcut, reveals the ambition of the successors to show the prestige of the House rather than to compensate for its lack on the book market. The first French translation that follows as quickly as a year after (1546) contains a new set of woodcuts, inspired by the originals but representing the Fontainebleau school. This edition is only the first one in a long chain of different ‘poliphilesque’ writings, quite different from the original and from one another, too, but able to ensure the popularity of the Hypnerotomachia up to the romantic era of the first half of the 19th century.